Ultra-High performance concrete (UHPC) with polypropylene (Pp) and steel Fibres: Investigation on the high temperature behaviour. (18th October 2021) - Sciarretta, Francesca; Fava, Stefano; Francini, Marco; Ponticelli, Luca; Caciolai, Mauro; Briseghella, Bruno; Nuti, Camillo
Highlights: High temperature strength of UHPC with PP/Steel fibre is experimentally assessed. Hybrid PP-steel reinforcement is needed for UHPC. The results and literature indicate the need to increase PP content. Abstract: Ultra-high performance concretes (UHPC) are advanced cement-based materials characterised by superior mechanical properties with respect to normal and high-strength concretes; however, their dense and compact matrix can facilitate the onset of spalling at high temperatures. This problem is often coped up by adding polypropylene (PP) fibres to the mix design, alone or with other types of fibres; steel fibres enhance the material's tensile capacity. The paper presents a series of tests on two UHPC types (150 and 180 N/mm2) with PP fibres (0.27% of volume) and variable content of steel fibres (0% to 1.92%), aimed at investigating the residual mechanical properties of the material after high temperature exposure. The experimental results are compared to available research on small UHPC specimens exposed to high temperatures, with dosages in PP fibres from 0.03% to 2%, and in steel fibres from 0 to 3%. The results of this research demonstrate that UHPCs need hybrid fibre reinforcement (PP + steel) to withstand high temperatures, and that the residual strength increases after 200 °C exposure, at all steel fibre dosages; this is in line with literature. Available research also shows that strength loss is possible in hot conditions, as found in the present research, while PP fibres alone do not always prevent the occurrence of spalling in small UHPC samples.